BROADENING OF STARTUP CULTURE AND SMALL BUSINESS SECTOR IN UZBEKISTAN - Dauletbaeva Ulzada Bakhadirovna (Journals Park Publishing, 2025)
This paper examines the development stages of small business and entrepreneurship in Uzbekistan. It highlights the key factors influencing the growth of entrepreneurship, including government policies, economic conditions, and financial support mechanisms. The study follows an IMRAD structure to analyze historical trends, current challenges, and future prospects. The findings suggest that Uzbekistan has made significant progress in fostering entrepreneurship but still faces challenges such as regulatory constraints and access to finance.